Familial Alzheimer’s disease mutations at position 22 of the amyloid β-peptide sequence differentially affect synaptic loss, tau phosphorylation and neuronal cell death in an ex vivo system - Tackenberg, Christian (PLoS One, 2020)
Familial forms of Alzheimer’s disease (AD) are caused by mutations in the presenilin genes or in the gene encoding for the amyloid precursor protein (APP). Proteolytic cleavage of APP generates the β-amyloid peptide (Aβ), which aggregates into amyloid plaques, one of the major hallmarks of AD. APP mutations within the Aβ sequence, so-called intra-Aβ mutations, cluster around position E693 of APP, which corresponds to position E22 in the Aβ sequence. One of these mutations is the Osaka mutation, E693Δ, which has unique aggregation properties with patients showing unusually low brain amyloid levels on amyloid PET scans. Despite intense research on the pathomechanisms of different intra-Aβ mutants, our knowledge is limited due to controversial findings in various studies. Here, we investigated in an ex vivo experimental system the neuro- and synaptotoxic properties of two intra-Aβ mutants with different intrinsic aggregation propensities, the Osaka mutation E22Δ and the Arctic mutation E22G, and compared them to wild-type (wt) Aβ. Experiments in hippocampal slice cultures from transgenic mice were complemented by treating wild-type slices with recombinantly produced Aβ40 or Aβ42 containing the respective intra-Aβ mutations. Our analyses revealed that wt Aβ and E22G Aβ, both recombinant and transgenic, caused a loss of dendritic spines along with an increase in tau phosphorylation and tau-dependent neurodegeneration. In all experiments, the 42-residue variants of wt and E22G Aβ showed stronger effects than the respective Aβ40 isoforms. In contrast, E22Δ Aβ neither reduced dendritic spine density nor resulted in increased tau phosphorylation or neuronal cell death in our ex vivo system. Our findings suggest that the previously reported major differences in the aggregation kinetics between E22G and E22Δ Aβ are likely reflected in different disease pathomechanisms.